(untitled) (Journal of Interdisciplinary Insights, 2024)
Chuanjiang Haozi, a traditional music originating from Sichuan Province and Chongqing, is a national intangible cultural heritage of China. Chuanjiang Haozi is the unified movement and rhythm of the boatmen, and it is the labor Haozi sung by the boatmen working in the Chuanjiang area of China. Led by the number worker and assisted by all the boatmen, it is a kind of folk singing form of leading and singing together. It is a song of life cast by blood and sweat when the boatmen fight against the dangerous shoals and vicious waters. Chuanjiang Haozi contains the spirit of perseverance, mutual help and cooperation, optimism and openness of the working people living in the river. This paper mainly focuses on Bayu folk music Chuanjiang Haozi as the research object, the first part introduces the geographical environment of Chuanjiang, the second part is the birth and development of Chuanjiang Haozi, the third part is the main concentrated form of Chuanjiang Haozi, more in-depth understanding of Chuanjiang Haozi. Focusing on the historical development of Chuanjiang Haozi, the study of its spiritual connotation and the inheritance of The Times will help us to better understand this folk art. Chuanjiang Haozi inherits the essence of Chinese national culture and contains a high value of music art.